The promotion effect of human activity intensity on displacement ventilation efficiency by the enhancement indoor thermal stratification - Chenlong Zhao; Bingye Song; Chenghao Zhang; Ran Gao; Long He (Case Studies in Thermal Engineering, 2024)
In a displacement ventilation system, the human body heat source plays a significant role and should not be overlooked. The intensity of human activity is a crucial factor in determining the amount of heat generated by the human body. In this work, the impact of thermal plumes generated by different levels of human activity intensity on the temperature stratification and ventilation efficiency in displacement ventilation system have been explored with experimental and numerical methods. The airflow patterns in the displacement air supply system under various levels of human activity intensity were simulated. The results show that under the same air supply speed, as the human activity intensity increasing from 125 W to 402 W, the phenomenon of temperature stratification becomes more pronounced. With the promotion of thermal plumes, the air flow velocity on the human body surface increases, leading to an enhancement in ventilation efficiency. Therefore, to elimination of the indoor thermal load, the air supply speed can be reasonably reduced according to the human activity intensity in the room, further enhancing the energy-saving effect of displacement ventilation.